Quality of Life of Chronic Kidney Failure Patients Treated at Dr. R. Koesma Tuban - Nadilla Shofiatul Ummah; Ummah1Teresia Retna Puspitadewi; Yasin Wahyurianto; Wahyuningsih Triana Nugrahaeni (Science Techno Health Journal, 2024)
Introduction: Chronic kidney failure (CKD) is a significant health problem throughout the world. The quality of life of a chronic kidney failure patient can decrease due to experiencing obstacles in carrying out activities. As a result, chronic kidney failure patients will withdraw from their environment and activities. Objective: The aim of this study is to describe the quality of life of chronic kidney failure patients treated at RSUD dr. R. Koesma Tuban. Method: Descriptive research design with a cross-sectional approach. The study population was patients with chronic kidney failure at RSUD dr. R. Koesma Tuban numbered 31 people, with a sample size of 31 people. The sampling technique used was total sampling. Research variables for quality of life in chronic kidney failure patients. Data was collected using a questionnaire and descriptive data analysis was carried out using frequency and percentage distribution tables. Results: The results of the study showed that all Chronic Kidney Failure patients treated at RSUD dr. R. Koesma Tuban, most (51.6%) aged 46-55 years, most (51.6%) male, almost half (35.40%), high school education level, most (61, 2%) do not work and the majority (58%) suffer <1 year. So chronic kidney failure patients have a very good quality of life. Almost all physical health domains are very good (80.6%), psychological health is mostly good (61.2%), social relationships are mostly good (61.2%), and relationships with the environment are mostly good (61.2% ). Conclusion: Efforts to improve patient quality of life by providing various interventions including education, prevention, early detection and appropriate management. Among other things, by providing appropriate education, providing comprehensive support, ensuring access to necessary care, health workers play an important role in reducing the incidence of CKD.